Management and outcome of extremely low birth weight infants - Apostolos Papageorgiou; Ermelinda Pelausa (Hygeia Press di Corridori Marinella, 2014)
Survival of extremely low birth weight (ELBW) and extremely premature (EP) infants has shown consistent improvement thanks to advances and innovations in perinatal and neonatal care. Regionalization, with high-risk deliveries in a tertiary perinatal center, offers the coordinated, collaborative, expert and specialized care needed by these mothers and their infants. Despite decreasing rates of the major neonatal morbidities observed in recent years, these continue still to be significant for ELBW/EP infants, impacting their overall prognosis. After NICU discharge and in the first years of life, issues with health, growth and development are common. In school age and adolescence, problems with behavior, socialization and cognition are prevalent. Adult outcomes of ELBW/EP need further clarity, emphasizing the importance for consistent long-term follow-up for this special cohort.   Proceedings of the 10th International Workshop on Neonatology · Cagliari (Italy) · October 22nd-25th, 2014 · The last ten years, the next ten years in Neonatology Guest Editors: Vassilios Fanos, Michele Mussap, Gavino Faa, Apostolos Papageorgiou